MODEL OF SOIL AND WATER CONSERVATION MEASURES APPLICATION BASED ON DISTRICT SPATIAL PLANNING IN MAMASA WATERSHED, SOUTH SULAWESI - Sri Malahayati Yusuf; Kukuh Murtilaksono; R.K. Astuti; Syaiful Arifin (Geoplanning: Journal of Geomatics and Planning, 2017)
Depletion of watershed carrying capacity cannot be omitted from mismanagement of the watershed. The integration between SWAT model and remote sensing data are able to identify, assess, and evaluate watershed problem as well as a tool to apply the mitigation of the problem. The aim of this study was to arrange the scenario of watershed management, and decide the best recommendation of sustainable watershed management of Mamasa Sub Watershed. The best recommendation was decided by hydrology parameters, e.i. surface runoff, sediment, and runoff coefficient. Hydrology characteristics of Mamasa Sub Watershed was analyzed based on land use data of year 2012 and climate data for period of 2010-2012. The scenarios were application of bunch and mulch in slope 1-15%; bunch terrace (scenario 1), mulch and strip grass in slope 15-25% (scenario 2), alley cropping in slope 25-40% (scenario 3), and combination scenario 1, 2, 3 with agroforestry in slope > 40% (scenario4). Surface runoff value of Mamasa Sub Watershed is 581.35 mm, while lateral flow, groundwater flow, runoff coefficient, and sediment yield of 640.72 mm, 228.17 mm, 0.29, and 187.213 ton/ha respectively. Based on the scenario’s simulation, the fourth scenario was able to reduce surface runoff and sediment yield of 33.441% and of 51.213%, while the runoff coefficient declined to 0.194. Thereby, the fourth scenario is recommended to be applied in Mamasa Sub Watershed so that the sustainability in the watershed can be achieved.